Control of Frequency Comb Spacing via Self-Crystallization of Dark Vectorial Solitons in Kerr Resonators - Campbell, Graeme N.; Hill, Lewis; Del’Haye, Pascal; Oppo, Gian Luca (Nonlinear Photonics, NP 2024 in Proceedings Advanced Photonics Congress 2024 - Part of Optica Advanced Photonics Congress, 2024)
Dark vectorial solitons in Kerr resonators with normal dispersion can spontaneously self-organize into regularly spaced crystals resulting in greater power and spacing of the frequency comb lines with increasing soliton numbers.
CRIS-Team Scopus Importer:2025-02-04